Driver licensing: descriptive epidemiology of a social determinant of Aboriginal and Torres Strait Islander health - Rebecca Q. Ivers; Kate Hunter; Kathleen Clapham; Yvonne Helps; Teresa Senserrick; Jake Byrne; Alexandra Martiniuk; John Daniels; James E. Harrison (Australian and New Zealand Journal of Public Health, 2016)
Abstract Objective: Education, employment and equitable access to services are commonly accepted as important underlying social determinants of health. For most Australians, access to health, education and other services is facilitated by private transport and a driver licence. This study aimed to examine licensing rates and predictors of licensing in a sample of Aboriginal and Torres Strait Islander people, as these have previously been poorly described. Methods: Interviewer‐administered surveys were conducted with 625 people 16 years or older in four Aboriginal Community Controlled Health Services in New South Wales and South Australia over a two‐week period in 2012–2013. Results: Licensing rates varied from 51% to 77% by site. Compared to not having a licence, having a driver licence was significantly associated with higher odds of full‐time employment (adjusted OR 4.0, 95%CI 2.5–6.3) and educational attainment (adjusted OR 1.9, 95%CI 1.2–2.8 for trade or certificate; adjusted OR 4.0, 95%CI 1.6–9.5 for degree qualification). Conclusions: Variation in driver licensing rates suggests different yet pervasive barriers to access. There is a strong association between driver licensing, education and employment. Implications: Licensing inequality has far‐reaching impacts on the broader health and wellbeing of Aboriginal and Torres Strait Islander people, reinforcing the need for appropriate and accessible pathways to achieving and maintaining driver licensing.